Om Chanting - Dimensions & Effects On Human Body, Mind & Soul (Journal of Namibian Studies : History Politics Culture, 2023)
OM-is the symbol of entire cosmos. No one & nothing can explain entirely the beauty & grandeur of OM .It’s like an ocean of  bliss . Vedic knowledge describes chakras[ plexus] which end at Sahasrar chakra [cosmic flower] & OM chanting helps to open petals of this psychic cosmic flower .The renowned iconic pose of Natraja is symbolization of victory of OM[Shiva] over  dwarf-devil [ignorance] named Apasmara Purusha owing to its movements & vibrations[ dance]. Different non- pharmaceutical methods are mentioned in Vedas & Upanishads like yoga, music , classical dance forms ,meditation ,chanting , praying; to mitigate negativity inside & outside us .This scientific Santana knowledge remained in dark due to invasions on India which caused destruction of many spiritual records. Meanwhile western medicine with its focus on anatomy replaced the established holistic model of Ayurveda. combining body, mind, spirit . In today’s world of unparalleled competition, industrialization ,24x7 work & life culture its but obvious for an individual to suffer from mental ailments at any point in life ; mantra meditation is the best method for beginners to ameliorate these ailments as it has both gross element[sound] & subtle element[vibrations]. Owing to modern neuro-scientific researches suggesting- religious practices have positive effects on brain functioning; tenets of ancient system have re-emerged & proving helpful in uncounted ways.